Diagnostic module for the radiation beam system “TEMP-B” - Batrakov, A.B.; Glushko, E.G.; Yegorov, А.М.; Zinchenko, A.A.; Lonin, Y.F.; Ponomarev, A.G.; Fedotov, S.I. (Вопросы атомной науки и техники, 2017)
The power module designed for the calibration and adjustment of the units and components of microsecond accelerator of relativistic electron beams (REB) “Temp-B” has been developed and manufactured. The noise immune gauge of high charging voltages of the terminal capacitors used by four-channel pulse voltage generator (PVG) and the discharger operating in the broad band of charging voltages have been manufactured. The methods developed using the module and the manufactured noise immune gauge of high charging voltages were applied to the accelerator “Temp-B”.